Biodegradable poly(ϵ-caprolactone) as a controlled drug delivery vehicle of vancomycin for the treatment of MRSA infection - Rai A.; Senapati S.; Saraf S.K.; Maiti P. (My University, 2025)
Biodegradable poly(ϵ-caprolactone) (PCL) is developed as a controlled drug delivery vehicle of vancomycin (VMC) with the advantage of avoiding a second surgery. The PCL-VMC hybrid, prepared through a solution route, is used as a delivery vehicle for vancomycin for controlling MRSA osteomyelitis as well as healing the cavity simultaneously in an experimental study. An in vitro study is conducted to optimize vancomycin impregnation in the PCL-VMC hybrid. An in vitro study on drug release from the hybrid material is investigated in phosphate buffer saline showing steady and sustained release of the drug. The release kinetics is fitted with several models and a non-Fickian nature is established following the Korsmeyer-Peppas model. Spectroscopic techniques and morphology observations reveal the cause of sustained release to be the strong interaction between the drug and the polymer. The results of the antibacterial assay show that the loading of vancomycin into the PCL matrix is able to maintain the activity of the pure drug. For the in vivo study, a unicortical defect is created in the metaphysis of the distal femur in rabbits. After contaminating the defect with MRSA, the 1st group of rabbits were treated with pure polymer, the 2nd group of rabbits were treated with normal saline (PBS), the 3rd group of rabbits were treated with pure VMC and in the last group of rabbits PCL-VMC was placed. Rabbits are assessed by clinical, radiological, histological, gross examination and bacterial load assays. Infection persisted throughout the period of study for both the pure polymer and PBS treated rabbits while rabbits treated with the PCL-VMC hybrid do not show any sign of infection. The VMC treated group rabbits show mild infection for the 1st week of the study; however, the infection becomes gradually more severe with time. Serial histology confirms the formation of new bone without any inflammation and necrosis for the rabbits treated with PCL-VMC. Importantly, the PCL-VMC hybrid bioadsorbs after delivery of the drug and thereby avoids the second surgery to remove the conventional implant. © The Royal Society of Chemistry 2016.